Foundation ActionScript for Flash 8 - Besley, Kristian; Bhangal, Sham; Dolecki, Eric; Powers, David (Apress : Imprint: Apress, 2006)
ActionScript is the native scripting language of Flash. ActionScript knowledge is essential within the world of Flash design and development, as Flash remains a leading tool for cutting-edge interactive design and development. ActionScript is what gives Flash its power, but with that power comes a certain level of complexity, which can be intimidating. This beginners' book, significantly updated since the last edition, covers all of the basics of ActionScript using version 8 of Flash. The skills acquired by working through this book will enable you to move on to more advanced friends of ED books, such as Foundation PHP 5 for Flash, Foundation ActionScript Animation or Foundation XML for Flash. This book contains all you need to understand and make use of ActionScript, and to have some fun while learning. The Foundation series teaching style is ideal if you're a non-programmer who wants to learn Flash programming quickly and thoroughly. The authors teach the basics, and provide an all-around proficiency in ActionScript, as well as Flash components within Flash 8. You'll gain the practical skills to build ActionScript based Flash projects, including making initial design decisions, structuring code, and testing. An ongoing case study means that by the end of the book, you'll have constructed a cutting-edge Flash site to showcase your newly learned skills.